2017
DOI: 10.1016/j.diabres.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimal glycemic target level for colon cancer patients with diabetes

Abstract: A optimal glycemic control level for colon cancer patients with diabetes should be recommended as an HbA1c of 7.8% or below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…By reading the full text, 101 studies were excluded for different reasons, and 5 studies did not provide sufficient data to calculate the outcome effect estimates. Finally, 36 studies were included in our meta-analysis[620, 2747]. The study selection process for inclusion in our meta-analysis was shown in Fig 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By reading the full text, 101 studies were excluded for different reasons, and 5 studies did not provide sufficient data to calculate the outcome effect estimates. Finally, 36 studies were included in our meta-analysis[620, 2747]. The study selection process for inclusion in our meta-analysis was shown in Fig 1.…”
Section: Resultsmentioning
confidence: 99%
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18 ] This lack of attention to their diabetes can affect their glycemic status and increase their risk for hospitalizations and increased symptom severity and may shorten their lives. [ 11 28 29 30 31 ] Adults with cancer and diabetes have a higher prevalence of nonadherence to their oral antidiabetic agents than adults with diabetes who do not have cancer, and this nonadherence increases the risk for poor glycemic control. Adherence to oral agents is associated with 24% fewer hospitalizations in cancer patients with diabetes.…”
Section: Glycemic Control and Survivorshipmentioning
confidence: 99%